An Enzymatically Hydrolyzed Animal Protein-Based Biostimulant (Pepton) Increases Salicylic Acid and Promotes Growth of Tomato Roots Under Temperature and Nutrient Stress - Casadesús, Andrea; Pérez-Llorca, Marina; Munné-Bosch, Sergi; Polo, Javier (Frontiers in Plant Science, 2020)
Biostimulants may be particularly interesting for application in agricultural and horticultural crops since they can exert a growth-promoting effect on roots. This may be important for promoting longitudinal and lateral root growth and therefore increasing belowground vegetative growth, which may in turn lead to improved aboveground vegetative growth and increased yields. Here, we examined the effects and mechanism of action of an enzymatically hydrolyzed animal protein-based biostimulant (Pepton) on the root growth of tomato plants, with an emphasis on its possible role on chorismate-derived hormones (auxin, salicylic acid and melatonin). Tomato plants growing in hydroponic systems were exposed to either nutrient stress conditions (experiment 1) or suboptimal temperatures (experiment 2) in a greenhouse, and the concentration of auxin, salicylic acid and melatonin in roots were measured just prior and after the application of the biostimulant. Results showed that the application of Pepton exerted a growth-promoting effect on roots in plants growing under suboptimal conditions, which might be associated with enhanced salicylic acid levels in roots. The extend of effects of this enzymatically hydrolyzed animal protein-based biostimulant might strongly depend on the growth conditions and stage of root system development. It is concluded that an enzymatically hydrolyzed animal protein-based biostimulant (Pepton) may exert a positive effect enhancing primary and lateral root growth of tomato plants growing under suboptimal conditions, by stimulating the biosynthesis of specific hormonal pathways, such as salicylic acid under stress.